Strong-waterproof and high-moisture-permeability outdoor jacket fabric and preparation method thereof

By introducing porous chitosan microspheres and aldehyde-based modified porous chitosan microspheres into the polyurethane film, it is solved by combining it with the woven fabric, and the tensile strength of the polyurethane film is reduced when improving moisture permeability is improved. , improves the breathable and moisture permeability of the fabric and realizes a strong waterproof and high moisture permeability jacket fabric.

CN119189451AActive Publication Date: 2024-12-27WUXI CENTURY WIND FASHION CO LTD

Patent Information

Application Number
CN202411505236.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2024-12-27
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

Existing polyurethane films will lead to a decrease in tensile strength when improving moisture permeability and lack the warmth improvement of windbreaker fabrics.

Method used

Porous chitosan microspheres and aldehyde-based modified porous chitosan microspheres form a double-layer structure TPU film, and is hot-pressed and composited with the woven fabric, and is heat-pressed to the insulation and keratinase treatment of porous chitosan microspheres It produces rough micropores to improve breathable moisture permeability, and at the same time introduces cerium-based complexes to improve warmth.

Benefits of technology

It significantly improves the mechanical properties, breathable and moisture permeability and warmth of the TPU film, and enhances the comfort and functionality of the jacket fabric.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a high-waterproof and high-moisture-permeability outdoor jacket fabric and a preparation method thereof, and relates to the technical field of fabrics. The preparation method comprises the following steps: step 1, preparation of the TPU film: preparing a spinning solution A and a spinning solution B containing different porous chitosan microsphere proportions; spinning the spinning solution A to obtain an inner layer; coating an aldehyde group modified porous chitosan microsphere solution on one side of the base membrane, spinning a spinning solution B on the surface of the base membrane by taking a coating surface as a receiving layer to obtain an outer layer, and drying to obtain a composite base membrane; putting the composite base membrane into a keratinase solution, and performing pretreatment; then coating a 3-sulfopropyl acrylate potassium salt mixed solution on the surface of the outer layer, and carrying out ultraviolet irradiation at room temperature; soaking in deionized water, and drying to obtain a TPU film; 2, the TPU film and the woven fabric are subjected to hot-pressing compounding, and the outdoor jacket fabric is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fabrics, in particular to a highly waterproof and highly moisture-permeable jacket fabric and a preparation method thereof. Background Art

[0002] In recent years, with the popularity of outdoor sports, the demand for outdoor sports equipment such as jackets has increased. Among them, jacket fabrics usually need to be waterproof, breathable, and warm.

[0003] In the prior art, polyurethane is a polymer material formed by polyisocyanate and polyhydroxy polymer, which is wear-resistant, highly elastic, and highly extensible, and can be well adapted to various morphological changes of clothing and various environmental uses; therefore, polyurethanes such as TPU films have been widely used in outdoor sports. At present, the polyurethane films obtained in the fabrics of assault jackets usually have microporosity, and the water molecules pass through the micropores to achieve air permeability and moisture permeability. However, the existing polyurethane films have the following disadvantages: In general, in order to improve the moisture permeability, the porosity needs to be increased, but this often leads to a decrease in mechanical properties such as tensile strength; on the other hand, if the porosity is not increased, the air permeability and moisture permeability will be affected. In addition, the existing polyurethane films usually do not involve improving the warmth retention of the fabrics of assault jackets.

[0004] In summary, it is of great significance to solve the defects of the prior art and prepare a jacket fabric. Summary of the invention

[0005] The object of the present invention is to provide a highly waterproof and highly breathable jacket fabric and a preparation method thereof, so as to solve the problems raised in the prior art.

[0006] To achieve the above object, the present invention provides the following technical solutions: A method for preparing a highly waterproof and highly breathable jacket fabric comprises the following steps: Step 1: Preparation of TPU film: S1-1: polyacrylonitrile and hydrophilic thermoplastic polyurethane elastomer are sequentially added to N,N-dimethylformamide, and porous chitosan microspheres in different proportions are added, and stirred at 55-60° C. for 4-5 hours to obtain spinning solution A and spinning solution B; S1-2: Spinning the spinning solution A to obtain an inner layer; coating one side of the spinning solution with an aldehyde-modified porous chitosan microsphere solution, using the coated surface as a receiving layer, spinning the spinning solution B on the surface to obtain an outer layer; drying the spinning solution at 60-70° C. for 2-4 hours to obtain a composite base membrane; S1-3: placing the composite base film in a keratinase solution and pre-treating it at 40-45°C for 6-8 hours; then coating the surface of the outer layer with a 3-sulfopropyl acrylate potassium salt mixed solution, irradiating it with ultraviolet light for 1-2 hours at room temperature; soaking it in deionized water for 1-2 days, and drying it to obtain a TPU film; Step 2: Hot-press the TPU film and the woven fabric to obtain the jacket fabric.

[0007] The woven fabric is interwoven with bi-component composite fiber yarns, and the bi-component composite fiber includes but is not limited to T800 stretch yarn, etc.; Among them, the jacket fabric prepared in the present application can be combined with other fabrics to further expand the functionality of the composite fabric. Other fabrics include but are not limited to knitted fabrics, waterproof fabrics, etc.

[0008] More optimally, the spinning solution A includes the following raw materials in parts by mass: 4 to 5 parts of polyacrylonitrile, 6 to 7 parts of hydrophilic thermoplastic polyurethane elastomer, 3 to 4 parts of porous chitosan microspheres, and 84 to 87 parts of N,N-dimethylformamide; the spinning solution B includes the following raw materials in parts by mass: 4 to 5 parts of polyacrylonitrile, 6 to 7 parts of hydrophilic thermoplastic polyurethane elastomer, 6 to 8 parts of porous chitosan microspheres, and 80 to 84 parts of N,N-dimethylformamide.

[0009] More optimally, the spinning parameters of the spinning solution A are: voltage of 18~20kV, receiving distance of 18~20cm, and injection speed of 0.1~0.11mL / min; the spinning parameters of the spinning solution B are voltage of 14~16kV, receiving distance of 14~16cm, and injection speed of 0.05~0.08mL / min.

[0010] More optimally, the preparation method of the porous chitosan microspheres is as follows: (1) 7-8 mg / mL chitosan-acetic acid aqueous solution, 3-4 mg / mL phosphorylated chitosan-acetic acid aqueous solution, 3-4 mg / mL keratin aqueous solution, and 0.1-0.15 mg / mL polyethylene glycol aqueous solution are mixed and stirred evenly to obtain an aqueous phase; (2) 0.1-0.12 g / mL Tween-20 is added to a mixed solvent of cyclohexane and n-hexanol to obtain an oil phase; (3) the aqueous phase is added dropwise to the oil phase and stirred to form an emulsion, and 0.08-0.12 g / mL glutaraldehyde aqueous solution is quickly injected, and stirred at 1000-1200 rpm for 6-8 hours, anhydrous ethanol is added and stirred for 1-2 hours, centrifuged, washed, and freeze-dried to obtain porous chitosan microspheres.

[0011] More optimally, in the raw materials of the aqueous phase, the volume ratio of chitosan-acetic acid aqueous solution, phosphorylated chitosan-acetic acid aqueous solution, keratin-aqueous solution, and polyethylene glycol aqueous solution is 4~5:2:3~4:0.2~0.3; the concentration of the acetic acid aqueous solution is 1~1.2wt%; the volume ratio of cyclohexane and n-hexanol is 60~70:30~40; the volume ratio of the aqueous phase, the oil phase, and the glutaraldehyde aqueous solution is 10:60:1~2.

[0012] Preferably, the concentration of the aldehyde-modified porous chitosan microsphere solution is 1-2 wt %, and the coating amount is 50-60 g / m 2 ; The impregnation ratio of the composite basement membrane to the keratinase solution is 1:5-8, and the amount of keratinase used is 120-150u / g based on the mass of the composite basement membrane; The coating amount of the 3-sulfopropyl acrylate potassium salt mixed solution is 100-160 g / m 2 .

[0013] More optimally, the preparation method of the aldehyde-modified porous chitosan microspheres is: adding porous chitosan microspheres to dimethyl sulfoxide, adding 2-iodoylbenzoic acid, stirring and reacting at 25-30° C. for 30-48 hours, and post-treating to obtain aldehyde-modified porous chitosan microspheres; the mass ratio of porous chitosan microspheres to 2-iodoylbenzoic acid is 1:0.3-0.5.

[0014] More optimally, the 3-sulfopropyl acrylate potassium salt mixed solution includes the following raw materials in parts by mass: 6 to 8 parts of 3-sulfopropyl acrylate potassium salt, 2 to 3 parts of cerium-based complex, 0.5 to 1 part of photoinitiator DMPA, and 100 parts of deionized water.

[0015] More optimally, the preparation method of the cerium-based complex is to add 4-allylcatechol, 3-aminomethylcatechol and cerium salt in a molar ratio of 1:1:1 to xylene in sequence, stir at 70-80°C for 1-2 hours, wash and dry to obtain the cerium-based complex.

[0016] More optimally, in the jacket fabric, the surface density of the TPU film is 30-50 g / m 2 .

[0017] Compared with the prior art, the present application has the following beneficial effects: In the (1) scheme, porous chitosan microspheres of different proportions are introduced into the spinning solution for spinning to form a TPU film with a double-layer structure; and aldehyde-modified chitosan is introduced between the double layers as an interface reinforcement layer; the mechanical properties, air permeability and moisture permeability of the TPU film are effectively improved. At the same time, the thermal insulation of the porous chitosan microspheres is used to effectively assist in improving the thermal insulation performance of the fabric.

[0018] Among them, porous chitosan microspheres are prepared from chitosan, phosphorylated chitosan, and keratin. Compared with microspheres produced by single chitosan, they have better pore stability and mechanical properties, thereby improving the mechanical properties and air permeability and moisture permeability of the TPU film. First, phosphorylated chitosan can provide additional cross-linking points to improve the mechanical strength of the microspheres, have better thermal stability, and thus improve the thermal insulation performance; second, the introduction of phosphorylated chitosan and keratin can change the pore structure of the microspheres and increase the porosity. Phosphorylation can increase the spacing between polymer chains, thereby increasing more air permeability and moisture permeability channels; and the addition of keratin may increase the flexibility and porosity of the microspheres, thereby enhancing their air permeability; thus, a mesh microsphere with multiple cross-linking and low thermal conductivity is produced, which can effectively improve the relevant performance.

[0019] Among them, porous chitosan microspheres are introduced into the spinning solution at different contents for spinning to form inner and outer layers with different contents, and then the keratin is roughened by the subsequent protein enzyme treatment process to produce rough micropores, which is conducive to the capillary effect, thereby achieving moisture permeability and heat insulation; and due to the different contents of the two layers, a wetting gradient difference is generated, thereby improving the one-way air permeability and moisture permeability, and increasing the comfort of the jacket fabric. In addition, in order to further increase the wetting gradient difference of the TPU film, the thiol group generated by the porous chitosan microspheres after keratinase treatment is used, and then 3-sulfopropyl acrylate potassium salt and cerium-based complex are grafted on one side; thereby effectively increasing the moisture permeability and air permeability. At the same time, the introduced cerium-based complex can effectively improve the far-infrared radiation and improve the warmth retention.

[0020] (2) In the scheme, the TPU film is compounded with the woven fabric, and the yarn of the outer woven fabric layer is made of two-component composite fiber yarn. The fabric has a soft and cottony feel and good elasticity, which improves the wearing experience. DETAILED DESCRIPTION

[0021] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.

[0022] It should be noted that the purchase manufacturers of all raw materials involved in the present invention are exemplified without any special restrictions: in the following embodiments, parts are parts by mass; the DAC of chitosan is greater than 90%, purchased from Shandong Haiyihua Biotechnology Co., Ltd.; the molecular weight of polyethylene glycol is 600; the product number of keratin is HC5162, purchased from Tianmen Hengchang Chemical Co., Ltd.; the CAS number of 2-iodoacylbenzoic acid is 61717-82-6, the CAS number of 3-aminomethylcatechol is 3-aminomethylcatechol, and the CAS number of 4-allylcatechol is 1126-61-0.

[0023] Preparation of phosphorylated chitosan: 10 g of chitosan was added to a 10 wt % acetic acid aqueous solution, stirred at room temperature for 30 minutes, 50 mL of a 20 wt % phosphoric acid solution was added, stirred at 50° C. for 2 to 3 hours, washed, and dried to obtain phosphorylated chitosan; Preparation of porous chitosan microspheres: (1) 7 mg / mL chitosan-acetic acid aqueous solution, 3 mg / mL phosphorylated chitosan-acetic acid aqueous solution, 3 mg / mL keratin aqueous solution, and 0.12 mg / mL polyethylene glycol aqueous solution were mixed and stirred to obtain an aqueous phase; (2) 0.1 g / mL Tween-20 was added to a mixed solvent of cyclohexane and n-hexanol (volume ratio of 70:30) to obtain an oil phase; (3) The aqueous phase was added dropwise to the oil phase and stirred to form an emulsion, and 0.08 g / mL of The glutaraldehyde aqueous solution is stirred at 1000 rpm for 8 hours, anhydrous ethanol is added and stirred for 1 hour, centrifuged, washed, and freeze-dried to obtain porous chitosan microspheres; wherein the volume ratio of chitosan-acetic acid aqueous solution, phosphorylated chitosan-acetic acid aqueous solution, keratin-aqueous solution, and polyethylene glycol aqueous solution is 4:2:3:0.2; the concentration of the acetic acid aqueous solution is 1wt%; the volume ratio of Tween-20, cyclohexane and n-hexanol included in the raw materials of the oil phase is; the volume ratio of the water phase, the oil phase and the glutaraldehyde aqueous solution is 10:60:1.5.

[0024] Preparation of aldehyde-modified porous chitosan microspheres: 1 part of porous chitosan microspheres was added to 50 parts of dimethyl sulfoxide, and 0.5 parts of 2-iodacylbenzoic acid were added, and stirred at 25°C for 48 hours, and post-treated to obtain aldehyde-modified porous chitosan microspheres; Preparation of cerium-based complex: 4-allylcatechol, 3-aminomethylcatechol and cerium sulfate hydrate in a molar ratio of 1:1:1 are added to xylene in sequence, stirred at 80° C. for 2 hours, washed and dried to obtain a cerium-based complex.

[0025] Embodiment 1: A method for preparing a highly waterproof and highly breathable jacket fabric, comprising the following steps: Step 1: Preparation of TPU membrane: S1-1: 4 parts of polyacrylonitrile and 6 parts of hydrophilic thermoplastic polyurethane elastomer are sequentially added to 87 parts of N, N-dimethylformamide, 3 parts of porous chitosan microspheres are added, and the mixture is stirred at 60°C for 4 hours to obtain a spinning solution A; 4 parts of polyacrylonitrile and 6 parts of hydrophilic thermoplastic polyurethane elastomer are sequentially added to N, N-dimethylformamide, 83 parts of N, N-dimethylformamide, 7 parts of porous chitosan microspheres are added, and the mixture is stirred at 60°C for 4 hours to obtain a spinning solution B; S1-2: The spinning solution A was electrospun at a voltage of 20 kV, a receiving distance of 18 cm, and a jet speed of 0.1 mL / min to obtain an inner layer; an aldehyde-modified porous chitosan microsphere solution with a concentration of 1.5 wt% was coated on one side of the inner layer, and the coating amount was 60 g / m 2 ; Using the surface as a receiving layer, electrospinning solution B on its surface at a voltage of 15 kV, a receiving distance of 15 cm, and a jet speed of 0.05 mL / min to obtain an outer layer; drying it at 65° C. for 2 hours to obtain a composite base film; S1-3: The composite base membrane is placed in a keratinase solution (the amount of keratinase to the composite base membrane mass is 140u / g), the immersion volume ratio is 1:5, and pre-treated at 45°C for 8 hours; then the outer surface is coated with a 3-sulfopropyl acrylate potassium salt mixed solution, the coating amount is 150g / m 2 , irradiated with ultraviolet light for 2 hours at room temperature; immersed in deionized water for 2 days, and dried to obtain a TPU film; The 3-sulfopropyl acrylate potassium salt mixed solution includes the following raw materials in parts by mass: 7 parts of 3-sulfopropyl acrylate potassium salt, 3 parts of cerium-based complex, 1 part of photoinitiator DMPA, and 100 parts of deionized water; Step 2: Overlay the TPU film and the woven fabric, set the pressure to 30 Pa, and hot-press and laminate at 130°C for 10 seconds to obtain the jacket fabric.

[0026] Embodiment 2: A method for preparing a highly waterproof and highly breathable jacket fabric, comprising the following steps: Step 1: Preparation of TPU membrane: S1-1: 5 parts of polyacrylonitrile and 7 parts of hydrophilic thermoplastic polyurethane elastomer are sequentially added to 84 parts of N,N-dimethylformamide, 4 parts of porous chitosan microspheres are added, and the mixture is stirred at 60°C for 4 hours to obtain a spinning solution A; 5 parts of polyacrylonitrile and 5 parts of hydrophilic thermoplastic polyurethane elastomer are sequentially added to N,N-dimethylformamide, 82 parts of N,N-dimethylformamide, 8 parts of porous chitosan microspheres are added, and the mixture is stirred at 60°C for 4 hours to obtain a spinning solution B; S1-2: The spinning solution A was electrospun at a voltage of 20 kV, a receiving distance of 18 cm, and a jet speed of 0.1 mL / min to obtain an inner layer; a 2 wt% aldehyde-modified porous chitosan microsphere solution was coated on one side thereof, and the coating amount was 50 g / m 2 ; Using the surface as a receiving layer, electrospinning solution B on its surface at a voltage of 15 kV, a receiving distance of 15 cm, and a jet speed of 0.05 mL / min to obtain an outer layer; drying it at 65° C. for 2 hours to obtain a composite base film; S1-3: The composite base membrane is placed in a keratinase solution (the amount of keratinase to the composite base membrane mass is 140u / g), the immersion volume ratio is 1:5, and pre-treated at 45°C for 8 hours; then the outer surface is coated with a 3-sulfopropyl acrylate potassium salt mixed solution, the coating amount is 150g / m 2 , irradiated with ultraviolet light for 2 hours at room temperature; immersed in deionized water for 2 days, and dried to obtain a TPU film; The 3-sulfopropyl acrylate potassium salt mixed solution includes the following raw materials in parts by mass: 6 parts of 3-sulfopropyl acrylate potassium salt, 2 parts of cerium-based complex, 0.5 parts of photoinitiator DMPA, and 100 parts of deionized water; Step 2: Overlay the TPU film and the woven fabric, set the pressure to 30 Pa, and hot-press and laminate at 130°C for 10 seconds to obtain the jacket fabric.

[0027] Embodiment 3: A method for preparing a highly waterproof and highly breathable jacket fabric, comprising the following steps: Step 1: Preparation of TPU membrane: S1-1: 5 parts of polyacrylonitrile and 5 parts of hydrophilic thermoplastic polyurethane elastomer are sequentially added to 87 parts of N,N-dimethylformamide, 3 parts of porous chitosan microspheres are added, and the mixture is stirred at 60°C for 4 hours to obtain a spinning solution A; 4 parts of polyacrylonitrile and 6 parts of hydrophilic thermoplastic polyurethane elastomer are sequentially added to N,N-dimethylformamide, 84 parts of N,N-dimethylformamide, 6 parts of porous chitosan microspheres are added, and the mixture is stirred at 60°C for 4 hours to obtain a spinning solution B; S1-2: The spinning solution A was electrospun at a voltage of 20 kV, a receiving distance of 18 cm, and a jet speed of 0.1 mL / min to obtain an inner layer; a 1 wt% aldehyde-modified porous chitosan microsphere solution was coated on one side thereof, and the coating amount was 60 g / m 2 ; Using the surface as a receiving layer, electrospinning solution B on its surface at a voltage of 15 kV, a receiving distance of 15 cm, and a jet speed of 0.05 mL / min to obtain an outer layer; drying it at 65° C. for 2 hours to obtain a composite base film; S1-3: The composite base membrane is placed in a keratinase solution (the amount of keratinase to the composite base membrane mass is 140u / g), the immersion volume ratio is 1:5, and pre-treated at 45°C for 8 hours; then the outer surface is coated with a 3-sulfopropyl acrylate potassium salt mixed solution, the coating amount is 150g / m 2 , irradiated with ultraviolet light for 2 hours at room temperature; immersed in deionized water for 2 days, and dried to obtain a TPU film; The 3-sulfopropyl acrylate potassium salt mixed solution includes the following raw materials in parts by mass: 8 parts of 3-sulfopropyl acrylate potassium salt, 2 parts of cerium-based complex, 1 part of photoinitiator DMPA, and 100 parts of deionized water; Step 2: Overlay the TPU film and the woven fabric, set the pressure to 30 Pa, and hot-press and laminate at 130°C for 10 seconds to obtain the jacket fabric.

[0028] Comparative Example 1: Single-layer TPU film, the rest is the same as Example 1, specifically comprising the following steps: Step 1: Preparation of TPU membrane: S1-1: 4 parts of polyacrylonitrile and 6 parts of hydrophilic thermoplastic polyurethane elastomer are sequentially added to 85 parts of N,N-dimethylformamide, and 5 parts of porous chitosan microspheres are added, and stirred at 60°C for 4 hours to obtain a spinning solution; S1-2: The spinning solution was electrospun at a voltage of 20 kV, a receiving distance of 18 cm, and a jet speed of 0.1 mL / min, and dried at 65° C. for 2 hours to obtain a composite base film; S1-3: The composite base membrane is placed in a keratinase solution (the amount of keratinase to the composite base membrane mass is 140u / g), the immersion volume ratio is 1:5, and pre-treated at 45°C for 8 hours; then the outer surface is coated with a 3-sulfopropyl acrylate potassium salt mixed solution, the coating amount is 150g / m 2 , irradiated with ultraviolet light for 2 hours at room temperature; immersed in deionized water for 2 days, and dried to obtain a TPU film; The 3-sulfopropyl acrylate potassium salt mixed solution includes the following raw materials in parts by mass: 7 parts of 3-sulfopropyl acrylate potassium salt, 3 parts of cerium-based complex, 1 part of photoinitiator DMPA, and 100 parts of deionized water; Step 2: Overlay the TPU film and the woven fabric, set the pressure to 30 Pa, and hot-press and laminate at 130°C for 10 seconds to obtain the jacket fabric.

[0029] Comparative Example 2: Using a single chitosan porous microsphere, the rest is the same as Example 1, except that: Preparation of porous chitosan microspheres: (1) 10 mg / mL chitosan-acetic acid aqueous solution and 0.15 mg / mL polyethylene glycol aqueous solution are mixed and stirred to obtain an aqueous phase; (2) 0.1 g / mL Tween-20 is added to a mixed solvent of cyclohexane and n-hexanol (volume ratio is 70:30) to obtain an oil phase; (3) the aqueous phase is added dropwise to the oil phase and stirred to form an emulsion, and 0.08 g / mL glutaraldehyde aqueous solution is quickly injected, stirred at 1000 rpm for 8 hours, anhydrous ethanol is added and stirred for 1 hour, centrifuged, washed, and freeze-dried to obtain porous chitosan microspheres; wherein the volume ratio of chitosan-acetic acid aqueous solution to polyethylene glycol aqueous solution is 4:0.1; the concentration of acetic acid aqueous solution is 1 wt%; the volume ratio of Tween-20, cyclohexane and n-hexanol included in the raw materials of the oil phase is; and the volume ratio of the aqueous phase, the oil phase and the glutaraldehyde aqueous solution is 10:60:1.5.

[0030] Comparative Example 3: The aldehyde-modified chitosan porous microspheres are not introduced into the TPU film; the rest is the same as Example 1, specifically comprising the following steps: Step 1: Preparation of TPU membrane: S1-1: 4 parts of polyacrylonitrile and 6 parts of hydrophilic thermoplastic polyurethane elastomer are sequentially added to 87 parts of N, N-dimethylformamide, 3 parts of porous chitosan microspheres are added, and the mixture is stirred at 60°C for 4 hours to obtain a spinning solution A; 4 parts of polyacrylonitrile and 6 parts of hydrophilic thermoplastic polyurethane elastomer are sequentially added to N, N-dimethylformamide, 83 parts of N, N-dimethylformamide, 7 parts of porous chitosan microspheres are added, and the mixture is stirred at 60°C for 4 hours to obtain a spinning solution B; S1-2: The spinning solution A was electrospun at a voltage of 20 kV, a receiving distance of 18 cm, and a spraying speed of 0.1 mL / min to obtain an inner layer; the inner layer was used as a receiving layer, and the spinning solution B was electrospun on its surface at a voltage of 15 kV, a receiving distance of 15 cm, and a spraying speed of 0.05 mL / min to obtain an outer layer; the outer layer was dried at 65° C. for 2 hours to obtain a composite base film; S1-3: The composite base membrane is placed in a keratinase solution (the amount of keratinase to the composite base membrane mass is 140u / g), the immersion volume ratio is 1:5, and pre-treated at 45°C for 8 hours; then the outer surface is coated with a 3-sulfopropyl acrylate potassium salt mixed solution, the coating amount is 150g / m 2 , irradiated with ultraviolet light for 2 hours at room temperature; immersed in deionized water for 2 days, and dried to obtain a TPU film; The 3-sulfopropyl acrylate potassium salt mixed solution includes the following raw materials in parts by mass: 7 parts of 3-sulfopropyl acrylate potassium salt, 3 parts of cerium-based complex, 1 part of photoinitiator DMPA, and 100 parts of deionized water; Step 2: Overlay the TPU film and the woven fabric, set the pressure to 30 Pa, and hot-press and laminate at 130°C for 10 seconds to obtain the jacket fabric.

[0031] Comparative Example 4: The composite base film is used as the TPU film, and the preparation steps are the same as those in Example 1.

[0032] Comparative Example 5: Jacket fabric purchased from the market, Shenzhen Jinhongsheng Textile Technology Co., Ltd., B42012.

[0033] Performance Test 1: The jacket fabrics in the embodiment and comparative example were subjected to the following tests; the hydrostatic pressure was based on GB / T4744-2013, and the test area was 100 cm 2 , the water pressure rise rate is 60cmH 2O / min, the test surface is woven fabric surface; water repellency refers to GB / T4745-2012 spray method, the test water temperature is 20℃, and the test surface is woven fabric surface; moisture permeability refers to GB / T12704.2-2009 method B, condition a, inverted cup method, the test chamber temperature is 38℃, the humidity is 50%, the wind speed is 0.3~0.5m / s, the back side faces the water, and the test surface is TPU film surface; the obtained data are shown in Table 1: Table 1

[0034] Conclusion: From the data in the above table, it can be seen that the jacket fabric prepared in the present application has excellent functionality, and its hydrostatic pressure, water repellency and moisture permeability are much higher than those of commercially available jacket fabrics.

[0035] Performance Test 1: The TPU films in the examples and comparative examples were subjected to the following performance tests; the tensile strength was tested using a universal mechanical tester at a tensile rate of 100 m / min; the thermal conductivity was tested using a 2 mm thick TPU film with the outer layer and the inner layer having the same thickness; the obtained data are shown in Table 2.

[0036] Table 2

[0037] Conclusion: From the data in the above table, it can be seen that the present application has prepared a TPU film with excellent mechanical properties and thermal insulation properties, which has excellent practicality when used for jacket fabrics.

[0038] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a highly waterproof and highly breathable jacket fabric, characterized in that: The following steps are involved: Step 1: Preparation of TPU film: S1-1: polyacrylonitrile and hydrophilic thermoplastic polyurethane elastomer are sequentially added to N,N-dimethylformamide, and porous chitosan microspheres in different proportions are added, and stirred at 55-60° C. for 4-5 hours to obtain spinning solution A and spinning solution B; S1-2: Spinning the spinning solution A to obtain an inner layer; coating one side of the spinning solution with an aldehyde-modified porous chitosan microsphere solution, using the coated surface as a receiving layer, spinning the spinning solution B on the surface to obtain an outer layer; drying the spinning solution at 60-70° C. for 2-4 hours to obtain a composite base membrane; S1-3: placing the composite base film in a keratinase solution and pre-treating it at 40-45°C for 6-8 hours; then coating the surface of the outer layer with a 3-sulfopropyl acrylate potassium salt mixed solution, irradiating it with ultraviolet light for 1-2 hours at room temperature; soaking it in deionized water for 1-2 days, and drying it to obtain a TPU film; Step 2: Hot-press the TPU film and the woven fabric to obtain the jacket fabric.

2. The method for preparing a highly waterproof and highly breathable jacket fabric according to claim 1, characterized in that: The spinning solution A comprises the following raw materials in parts by mass: 4 to 5 parts of polyacrylonitrile, 6 to 7 parts of hydrophilic thermoplastic polyurethane elastomer, 3 to 4 parts of porous chitosan microspheres, and 84 to 87 parts of N,N-dimethylformamide; the spinning solution B comprises the following raw materials in parts by mass: 4 to 5 parts of polyacrylonitrile, 6 to 7 parts of hydrophilic thermoplastic polyurethane elastomer, 6 to 8 parts of porous chitosan microspheres, and 80 to 84 parts of N,N-dimethylformamide.

3. The method for preparing a highly waterproof and highly breathable jacket fabric according to claim 1, characterized in that: The spinning parameters of the spinning solution A are: voltage of 18-20 kV, receiving distance of 18-20 cm, and injection speed of 0.1-0.11 mL / min; the spinning parameters of the spinning solution B are: voltage of 14-16 kV, receiving distance of 14-16 cm, and injection speed of 0.05-0.08 mL / min.

4. The method for preparing a highly waterproof and highly breathable jacket fabric according to claim 1, characterized in that: The preparation method of the porous chitosan microspheres is as follows: (1) mixing 7-8 mg / mL chitosan-acetic acid aqueous solution, 3-4 mg / mL phosphorylated chitosan-acetic acid aqueous solution, 3-4 mg / mL keratin aqueous solution, and 0.1-0.15 mg / mL polyethylene glycol aqueous solution, stirring evenly to obtain an aqueous phase; (2) adding 0.1-0.12 g / mL Tween-20 to a mixed solvent of cyclohexane and n-hexanol to obtain an oil phase; (3) dropping the aqueous phase into the oil phase and stirring to form an emulsion, quickly injecting 0.08-0.12 g / mL glutaraldehyde aqueous solution, stirring at 1000-1200 rpm for 6-8 hours, adding anhydrous ethanol and stirring for 1-2 hours, centrifuging, washing, and freeze-drying to obtain porous chitosan microspheres.

5. The method for preparing a highly waterproof and highly breathable jacket fabric according to claim 4, characterized in that: Among the raw materials of the aqueous phase, the volume ratio of chitosan-acetic acid aqueous solution, phosphorylated chitosan-acetic acid aqueous solution, keratin-aqueous solution, and polyethylene glycol aqueous solution is 4-5:2:3-4:0.2-0.3; the concentration of the acetic acid aqueous solution is 1-1.2wt%; the volume ratio of cyclohexane and n-hexanol is 60-70:30-40; and the volume ratio of the aqueous phase, the oil phase, and the glutaraldehyde aqueous solution is 10:60:1-2.

6. The method for preparing a highly waterproof and highly breathable jacket fabric according to claim 1, characterized in that: The concentration of the aldehyde-modified porous chitosan microsphere solution is 1-2 wt %, and the coating amount is 50-60 g / m 2 ; The impregnation ratio of the composite basement membrane to the keratinase solution is 1:5-8, and the amount of keratinase used is 120-150u / g based on the mass of the composite basement membrane; The coating amount of the 3-sulfopropyl acrylate potassium salt mixed solution is 100-160 g / m 2 .

7. The method for preparing a highly waterproof and highly breathable jacket fabric according to claim 1, characterized in that: The preparation method of the aldehyde-modified porous chitosan microspheres comprises: adding the porous chitosan microspheres to dimethyl sulfoxide, adding 2-iodoxybenzoic acid, stirring and reacting at 25-30° C. for 30-48 hours, and post-treating to obtain the aldehyde-modified porous chitosan microspheres; the mass ratio of the porous chitosan microspheres to the 2-iodoxybenzoic acid is 1:0.3-0.

5.

8. The method for preparing a highly waterproof and highly breathable jacket fabric according to claim 1, characterized in that: The 3-sulfopropyl acrylate potassium salt mixed solution comprises the following raw materials in parts by weight: 6-8 parts of 3-sulfopropyl acrylate potassium salt, 2-3 parts of cerium-based complex, 0.5-1 part of photoinitiator DMPA, and 100 parts of deionized water.

9. The method for preparing a highly waterproof and highly breathable jacket fabric according to claim 8, characterized in that: The preparation method of the cerium-based complex comprises the following steps: adding 4-allylcatechol, 3-aminomethylcatechol and cerium salt in a molar ratio of 1:1:1 to xylene in sequence, stirring at 70-80° C. for 1-2 hours, washing and drying to obtain the cerium-based complex.

10. The jacket fabric prepared by the method for preparing a highly waterproof and highly breathable jacket fabric according to any one of claims 1 to 9, characterized in that: The surface density of the TPU film is 30-50 g / m 2 .

Citation Information

Patent Citations

  • Multi-layered film, method for the production and use thereof

    CA3047197A1

  • Cleaning enzymes and malodor prevention

    CN102604753A

  • Breathable and moisture-permeable composite TPU material and preparation method thereof

    CN117779351A

  • Benefit agent containing delivery particle

    US20080118568A1

  • Water-soluble films, water-soluble unit dose articles, and methods of making and using the same

    US20220186159A1

Cited By

  • Breathable waterproof composite fabric and preparation method thereof

    CN121675245A

  • Air-permeable waterproof composite fabric and preparation method thereof

    CN121675245B